Promoting Best Practice for E-tutoring through Staff Development - Gerrard, Catherine (Proceedings of the International Conference on Networked Learning, 2002)
The continuous stampede into the distance learning market combined with the introduction of virtual learning environments into on-campus courses in order to increase student numbers, widen access and meet the demands of lifelong learning, now places greater demands on face-to-face teaching staff. However, the cyberspace classroom is quite different from that of the face-to-face classroom and substantial pedagogical shifts will be required for successful online learning. But what is being done to help traditional teaching staff cope with these new pedagogical shifts? How will traditional teaching staff move from teaching in front of a class to teaching in the online environment? This paper will present the arguments that suggest that there is a need for staff who have only taught in the face-to-face situation to receive comprehensive training for their new online role if they are to meet the challenges and demands that online learning/teaching presents.